Orebody Characterization And Resource Management At De Beers Marine - Ian B. Corbett (International Marine Minerals Society, 1998)
De Beers Marine Pty Ltd. (South Africa) (DEBMARINE), a wholly owned subsidiary of De Beers Consolidated Mines Ltd. specializes in the provision of contracting and consulting services for offshore diamond exploration, Mineral Resource Management and mining. Established in 1983, the company is strongly focused on driving and sustaining growth of the offshore diamond mining industry into the 21st century. DEBMARINE provides full Mineral Resource Management and produce almost half a million carats annually for the Namibian Diamond Corporation (Pty) Ltd. from their offshore mining licence. The company is also extensively involved in feasibility studies to establish new mining ventures and in the exploration of several offshore Prospecting Licence Areas for other clients. As a pioneer in this field, DEBMARINE remains highly focused on technological development. A specialized section, the Technical Development Business Unit, has been established. Through relationships with various technology leaders, this unit develops new sub-sea mining technology and delivers productivity innovations aimed at realizing maximized carat extraction. This talk provides a broad perspective on the development of the Namibian offshore deposits and examines the critical role played by high-resolution orebody characterization and high-confidence Mineral Resource development at De Beers Marine.